Examining the impact of religiosity and environmental concern on switching behavior of Islamic digital-only bank users - Azhar Alam; Diajeng Dewi Mashitoh; Afief El Ashfahany; Fauziah Hassan; Mohd Yousuf Javed (Banks and Bank Systems, 2025)
In light of the fast expansion of digital banking, it is of the utmost importance to know the causes driving the acceptance of Islamic digital-only banks, particularly in Indonesia, which has a considerable Muslim population. This study examines the influence of religiosity and environmental concern on switching behavior towards Islamic digital-only banks in Indonesia. This study conducts an exploratory examination of how religiosity and environmental concerns influence switching behavior towards Islamic digital-only banks. Data from a survey involving 99 respondents in Indonesia were examined utilizing structural equation modeling with partial least squares (SEM-PLS). The study’s findings show that environmental concern significantly influences switching behavior to Islamic digital-only banks, with a path coefficient of 0.259 (p < 0.01). Religiosity also positively affects switching behavior, though with a weaker effect (path coefficient 0.175, p < 0.05). Environmental concern emerged as a stronger predictor of switching intentions compared to religiosity. The model explains 13.6% of the variance in switching behavior (R² = 0.136). These findings reveal that environmental considerations and religiosity play a role in shaping switching intentions towards Islamic digital-only banks, with environmental factors having a more pronounced effect. To promote adoption, Islamic digital-only banks should emphasize their environmental benefits and sustainability initiatives in addition to Sharia compliance.